2006
DOI: 10.1002/dneu.20306
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin decreases generation of dopaminergic neurons from mesencephalic precursors via serotonin type 7 and type 4 receptors

Abstract: Inductive signals mediating the differentiation of neural precursors into serotonergic (5-HT) or dopaminergic neurons have not been clarified. We have recently shown that in cell aggregates obtained from rat mesencephalic precursors, reduction of serotonin levels induces a marked increase in generation of dopaminergic neurons. In the present study we treated rat neurospheres with antagonists of the main subtypes of 5-HT receptors, 5-HT transport inhibitors, or 5-HT receptor agonists, and studied the effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Although depletion of serotonin reduces adult neurogenic outcome in rats [56], elevated levels of serotonin in serotonin transporter (SERT)-deficient mice did not affect NSC proliferation and neurogenesis [57,58]. In mesencephalic and hippocampal progenitors of mouse brain, inhibition of serotonin receptors or knocking out serotonin-producing enzymes to generate hyposerotonergic phenotypes had positive effects on neurogenesis [59][60][61][62] ascertaining a negative role for serotonin on NSC plasticity. These findings indicate that the effects of serotonin on NSCs are context dependent and may run through intermediary secondary signaling mechanisms, which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although depletion of serotonin reduces adult neurogenic outcome in rats [56], elevated levels of serotonin in serotonin transporter (SERT)-deficient mice did not affect NSC proliferation and neurogenesis [57,58]. In mesencephalic and hippocampal progenitors of mouse brain, inhibition of serotonin receptors or knocking out serotonin-producing enzymes to generate hyposerotonergic phenotypes had positive effects on neurogenesis [59][60][61][62] ascertaining a negative role for serotonin on NSC plasticity. These findings indicate that the effects of serotonin on NSCs are context dependent and may run through intermediary secondary signaling mechanisms, which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor has been found to influence cognitive functions and affective symptoms and interestingly, studies have shown that the 5-HT 4 R seems to exert control over dopamine transmission (Parga et al, 2007;Porras et al, 2002). Animal studies have identified the 5-HT 2C , 5-HT 1B , and 5-HT 6 receptors as influencing food intake and these receptors are considered as pharmacological anti-obesity targets (Garfield and Heisler, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…This is confirmed by an increase in generation of dopamine neurons after elimination of the 5-HT neurons or reduction of 5-HT levels using methiothepin (5-HT1,2,5,6,7 receptor antagonist), and the 5-HT7Rs antagonist SB 269,970. 52 …”
Section: Resultsmentioning
confidence: 99%